Cooperative design, visualization, and engineering : 12th International Conference, CDVE 2015, Mallorca, Spain, September 20-23, 2015, Proceedings /: 12th International Conference, CDVE 2015, Mallorca, Spain, September 20-23, 2015, Proceedings. (2015) - Unknown
No abstract available